Exploring Ways and Mechanisms for Farmers’ Cooperatives to Participate in Rural Public Services - Liu, Zhenhang; Fu, Peng (Transactions on Social Science, Education and Humanities Research, 2024)
From the perspective of the path and mechanisms of rural integration, this article explores the logic behind the integration of cooperatives into rural governance, using the Hongyuan Farmers’ Cooperative in Binchuan County, Dali City, Yunnan Province, as a case study.By leading villagers in development initiatives and embedding itself culturally and socially, the cooperative uses its organisational advantages to promote the healthy economic growth of villages and foster harmonious livelihoods among villagers. Through specific benefit-sharing mechanisms, the cooperative provides governance resources to the village collective, thereby strengthening the community’s governance capacity. As the development of the farmers’ cooperative progresses, the joint development of rural economic and public governance goals leads to the gradual formation of a new rural governance community.Practical experience shows that integrating the institutional strengths of farmers’ cooperatives into rural governance, coupled with internal and external policy management, reshapes the governance structure of different rural governance units. This becomes a new direction for promoting the modernisation of rural governance systems and governance capacities. In essence, this article highlights how the cooperative, by integrating itself culturally and economically into the village, not only promotes economic growth but also empowers villagers to live harmoniously. Moreover, the incorporation of the cooperative’s institutional strengths into rural governance redefines the structure of rural management units, suggesting a promising way to modernise rural governance systems.